2011
DOI: 10.1007/s10067-011-1831-1
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis in Burkina Faso: clinical and serological profiles

Abstract: The objective of this work was to study the clinical and serological profiles of rheumatoid arthritis in Burkina Faso (West Africa). It is a cross-sectional study conducted from March 2006 to February 2009 in the Internal Medicine Department of the University Hospital Yalgado Ouedraogo. All patients seen in the rheumatologic consultation unit during this period, with rheumatoid arthritis fulfilling the ACR criteria, were routinely selected. The determination of anticyclic citrullinated peptide antibodies (ACPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 12 publications
5
14
0
6
Order By: Relevance
“…The strong seropositivity to the rheumatoid factor (54.5%) and to the anti-CCP antibodies (89.2%) noted in this study was also reported by Ndongo (rheumatoid factor: 78% and anti-CCP: 90%) [25] and by Ouédraogo (rheumatoid factor: 70% and anti-CCP: 80%) [24]. In the western literature we note the prevalence of the factor and superimpose able antibodies anti-CCP to these data [29] [30] [31].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The strong seropositivity to the rheumatoid factor (54.5%) and to the anti-CCP antibodies (89.2%) noted in this study was also reported by Ndongo (rheumatoid factor: 78% and anti-CCP: 90%) [25] and by Ouédraogo (rheumatoid factor: 70% and anti-CCP: 80%) [24]. In the western literature we note the prevalence of the factor and superimpose able antibodies anti-CCP to these data [29] [30] [31].…”
Section: Discussionsupporting
confidence: 85%
“…In a study assessing the structural damage in the RA in Benin Zomalhèto, et al listed some characteristic articular deformations in 7 cases in 10 and over half of patients had a score of Larsen superior to 40 [23]. In Burkina, 9 patients in 10 presented at least a stage II of radiological Steinbrecher according to Ouédraogo et al [24].…”
Section: Discussionmentioning
confidence: 99%
“…The Journal of on May 9, 2018 -Published by www.jrheum.org Downloaded from Burkina Faso (81%), Egypt (85%), Cameroon (95%), and Senegal (91%) 3,31,32,33 . Thus, there seems to be a rather uniform finding of a higher female preponderance of RA in Africa as compared with in Europe.…”
Section: Rheumatologymentioning
confidence: 99%
“…RA presently constitutes 10 -15% of the rheumatologic cases seen in many of the rheumatology clinics in Nigeria(unreported observation). Other reports from Burkina Faso [9]; Kenya [10]; Cameroun [11]; South Africa [12]; Democratic Republic of Congo [13]; Senegal [14]; Zambia [15] also indicate that this condition may not be rare after all.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%